Presymptomatic detection and prenatal diagnosis for myotonic dystrophy by means of linked DNA markers. - Norman, A M (1989)
The close genetic linkage between the loci for apolipoprotein CII (ApoCII) and myotonic dystrophy makes presymptomatic detection and prenatal diagnosis feasible. We report three years' service experience of providing presymptomatic detection and prenatal diagnosis for myotonic dystrophy in 99 families. Careful clinical study of older family members remains important. The introduction of new probes (CKMM and BCL4) has helped to solve the problem of uninformativeness owing to unhelpful genotype distribution in a family. Nevertheless, informativeness cannot be guaranteed and families should be studied before pregnancy is undertaken whenever possible. Presymptomatic testing and prenatal diagnosis for myotonic dystrophy are soundly based. All affected subjects should have DNA banked for future use when other family members may require genotype information.